Simultaneous occurrence of structure-directed and particle-resonance-induced phononic gaps in colloidal films - T. Still; W. Cheng; M. Retsch; R. Sainidou; J.J. Wang; U. Jonas; N. Stefanou; G. Fytas (Physical Review Letters, 2008)
We report on the observation of two hypersonic phononic gaps of different nature in three-dimensional colloidal films of nanospheres using Brillouin light scattering. One is a Bragg gap occurring at the edge of the first Brillouin zone along a high-symmetry crystal direction. The other is a hybridization gap in crystalline and amorphous films, originating from the interaction of the band of quadrupole particle eigenmodes with the acoustic effective-medium band, and its frequency position compares well with the computed lowest eigenfrequency. Structural disorder eliminates the Bragg gap, while the hybridization gap is robust.